2005
DOI: 10.1111/j.1365-3156.2004.01352.x
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in parasitic infections, perceived ill health and access to health care among poorer and less poor schoolchildren of rural Côte d'Ivoire

Abstract: SummaryDifferences in the state of health between rural and urban populations living in Africa have been described, yet only few studies analysed inequities within poor rural communities. We investigated disparities in parasitic infections, perceived ill health and access to formal health services among more than 4000 schoolchildren from 57 primary schools in a rural area of western Cô te d'Ivoire, as measured by their socioeconomic status. In a first step, we carried out a cross-sectional parasitological surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
89
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(100 citation statements)
references
References 37 publications
10
89
0
1
Order By: Relevance
“…We also showed that many of the dense households were similar in HWI to those in dispersed households. Recently asset-based indices as a measure of wealth have been shown to not only be a more reliable index of wealth under conditions of extreme poverty, but also to be related to health outcomes, including improved nutritional status 37,38 and reduced parasitic infections, 39,40 an observation consistent with our findings. In rural areas where income is inconsistent, asset-based indices are considered a valuable proxy for relative standard of living, which was of particular interest in our study area where wage work is extremely rare and variables such as number of wage earners or income would not capture household financial status.…”
Section: Discussionsupporting
confidence: 82%
“…We also showed that many of the dense households were similar in HWI to those in dispersed households. Recently asset-based indices as a measure of wealth have been shown to not only be a more reliable index of wealth under conditions of extreme poverty, but also to be related to health outcomes, including improved nutritional status 37,38 and reduced parasitic infections, 39,40 an observation consistent with our findings. In rural areas where income is inconsistent, asset-based indices are considered a valuable proxy for relative standard of living, which was of particular interest in our study area where wage work is extremely rare and variables such as number of wage earners or income would not capture household financial status.…”
Section: Discussionsupporting
confidence: 82%
“…Although the high percentage of intestinal protozoa in these children could be attributed to feces-polluted water, protozoa in particular were not associated with SEV. In this sense, Raso et al (2005) demonstrated that high prevalences of protozoa (i.e. B. hominis, E. nana and I. butschlii) were not indicative of poverty since they were more frequently observed in higher income groups.…”
Section: Discussionmentioning
confidence: 98%
“…Local risk factors sustaining helminth transmission can include specific environmental differences, such as soil composition and moisture, as well as socioeconomic discrepancies and differences in sanitation, hygiene, and health-seeking behavior. 12,[40][41][42][43][44] The lack of detailed appraisal of some of these risk factors is a limitation of this study and is the focus of our ongoing work. The observed higher risk for boys to be infected with hookworm coincides with findings from Pemba and elsewhere in Africa and might result from behavioral, immunological, or genetic idiosyncracies.…”
Section: Discussionmentioning
confidence: 99%